Critical social work theories and practices for a socially just world - Allan, June editor; Briskman, Linda editor; Pease, Bob editor (Allen & Unwin, 2009)
"This second edition of 'Critical social work' has been thoroughly revised to take into account recent social, economic and political developments. Coverage of theoretical frameworks has been substantially expanded and reflects current concerns such as evidence-based practice and human rights. The causes of people's marginalization and oppression are examined in relation to class, race, ethnicity, gender and other forms of social inequality. Case study chapters in the earlier edition on working with immigrants, Indigenous people, women, men, families, people with psychiatric disabilities and those experiencing loss and grief have been updated and revised. The second edition includes new case study chapters on disability, older people, children, rurality, and violence and abuse."